2003
DOI: 10.1080/1071576031000099830
|View full text |Cite
|
Sign up to set email alerts
|

Myeloperoxidase has Directly-opposed Effects on Nitration Reaction--Study on Myeloperoxidase-deficient Patient and Myeloperoxidase-knockout Mice

Abstract: Myeloperoxidase (MPO) catalyzes a nitration reaction to form nitrotyrosine in the presence of high nitrite, the metabolite of NO. Human leukocyte was shown to cause phenolic nitration using released MPO as a catalyst in the presence of nitrite. It opposes our previous finding that inhibition of MPO was essential for phenol nitration in human leukocyte study. To clarify the role of MPO, we utilized MPO-deficient human leukocytes and MPO-knockout mice. Even in the absence of exogenously added nitrite, high nitra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…It has been debated whether this mechanism is the primary source of NT (Baldus et al, 2002). Though reports show MPO knockouts still have nitration (Ichimori et al, 2003), it has been shown that numerous heme and transition metal complexes can also generate NT . A comparison of NT at more physiologically relevant fluxes of NO and O 2 − clearly shown that nitration really occurs only when the fluxes are 1:1 (Espey et al, 2002a(Espey et al, , 2002b.…”
Section: Indirect Effects Of No: Rnsmentioning
confidence: 99%
“…It has been debated whether this mechanism is the primary source of NT (Baldus et al, 2002). Though reports show MPO knockouts still have nitration (Ichimori et al, 2003), it has been shown that numerous heme and transition metal complexes can also generate NT . A comparison of NT at more physiologically relevant fluxes of NO and O 2 − clearly shown that nitration really occurs only when the fluxes are 1:1 (Espey et al, 2002a(Espey et al, , 2002b.…”
Section: Indirect Effects Of No: Rnsmentioning
confidence: 99%
“…In particular, the MPO-specific anti-neutrophil cytoplasmic autoantibodies (MPO-ANCA, usually known as perinuclaear ANCA, p-ANCA) are significantly involved in the development of various kinds of vasculitis, including ANCA-associated rapid progressive glomerulonephritis (RPGN), and microscopic polyangiitis [6][7][8][9]. Previous studies have demonstrated that MPO is a major antigen for p-ANCA production by using MPO-deficient mice [10,11], and the adoptive transfer of MPO-reactive splenocytes into Rag2-deficient mice resulted in crescentic glomerulonephritis with a high MPO-ANCA titer [12]. The fact that high levels of MPO-ANCA resulted in kidney dysfunction is consistent with the observation that patients with ANCA-related RPGN showed significantly increased MPO activity and MPO-ANCA titer [13].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that enzymatic activity of serum MPO level was elevated in neutrophils and marked higher ANCA titers in Candida-induced coronary vasculitis mice, similar to the same features in SCG/Kj mice (38). In addition, the ANCA titer is dramatically diminished in MPO-deficient mice (3,19), indicating that fungal infection has relevance to the MPO molecule. Evidence suggests that MPO is an essential enzyme to protect fungal infection, and the overactivation of MPO could be a risk factor for arterial vasculitis formation.…”
Section: Discussionmentioning
confidence: 95%
“…In particular, the MPO-specific anti-neutrophil cytoplasmic autoantibody (MPO-ANCA) is significantly involved in the development of various kinds of vasculitis, ANCAassociated rapid progressive glomerulonephritis (RPGN), and microscopic polyangiitis (11,15,30,34). We and other groups have demonstrated that MPO is a major antigen for MPO-ANCA production by using MPO-deficient mice (3,19), and adoptive transfer of MPO-reactive splenocytes into Rag2-deficient mice resulted in crescentic glomerulonephritis with high MPO-ANCA titer (53). Furthermore, we have shown the contribution of activated neutrophils in renal lesions using spontaneous crescentic glomerulonephritis-forming mouse/Kinjoh (SCG/Kj) glomerulonephritis model mice (12,20).…”
mentioning
confidence: 99%